2000
DOI: 10.1093/jn/130.9.2151
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic LDL Receptor mRNA in Rats Is Increased by Dietary Mushroom (Agaricus bisporus) Fiber and Sugar Beet Fiber

Abstract: Plasma cholesterol concentration is reduced by feeding some dietary fibers and mushroom fruit body, but the mechanism is not fully understood. We examined the effects of mushroom (Agaricus bisporus) fiber and sugar beet fiber on serum cholesterol and hepatic LDL receptor mRNA in rats. Rats were fed a cholesterol-free diet with 50 g/kg cellulose powder (CP), 50 g/kg mushroom (Agaricus bisporus) fiber (MSF) or 50 g/kg sugar beet fiber (BF) for 4 wk. There were no significant differences in the body weight, food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
2
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 26 publications
5
62
2
3
Order By: Relevance
“…Fibers, ethanolic extracts Antioxidant (Wang et al, 1995(Wang et al, & 1996, Hypocholesterolemic (Fukushima et al, 2000(Fukushima et al, & 2001, Antiallergic (Sano et al, 2002) Grifola frondosa (Dicks.) Gray MD-fraction, ergosterol (1) Antioxidant (Wang et al, 1995(Wang et al, & 1996, hypotensive, Hypoglycemic (Horio et al, 2001), Immunotherapy (Hazama et al, 1995), Antiinflammatory activity (Zhang et al, 2002) Ganoderma lucidum (Curtis) P. Karst Ganoderan A and B, glucans, Triterpenes (ganoderiol F (2), ganodermanontriol (3), ganoderic acids (4) A, B, D, F, G, H, Z), ganosporeric acid A, ganopoly, the polysaccharide-containing preparation Hypoglycemic (Hikino et al, 1985), antioxidant and antitumor (Thekkuttuparambil et al, 2007), antiviral (HIV-1) (El-Mekkawy et al, 1998), Antiallergic (Kohda et al, 1985;Tasaka et al, 1988), Anti-inflammatory (Koyama et al, 1997), antihepatotoxic (Hirotani et al, 1986;Chen & Yu, 1993, inhibit the biosynthesis of cholesterol (Komoda et al, 1989), antioxidative and free radical scavenging effects (Lin, 2004) Ganoderma pfeifferi Bres.…”
Section: Flammulina Velutipes (Curtis) Singermentioning
confidence: 99%
See 1 more Smart Citation
“…Fibers, ethanolic extracts Antioxidant (Wang et al, 1995(Wang et al, & 1996, Hypocholesterolemic (Fukushima et al, 2000(Fukushima et al, & 2001, Antiallergic (Sano et al, 2002) Grifola frondosa (Dicks.) Gray MD-fraction, ergosterol (1) Antioxidant (Wang et al, 1995(Wang et al, & 1996, hypotensive, Hypoglycemic (Horio et al, 2001), Immunotherapy (Hazama et al, 1995), Antiinflammatory activity (Zhang et al, 2002) Ganoderma lucidum (Curtis) P. Karst Ganoderan A and B, glucans, Triterpenes (ganoderiol F (2), ganodermanontriol (3), ganoderic acids (4) A, B, D, F, G, H, Z), ganosporeric acid A, ganopoly, the polysaccharide-containing preparation Hypoglycemic (Hikino et al, 1985), antioxidant and antitumor (Thekkuttuparambil et al, 2007), antiviral (HIV-1) (El-Mekkawy et al, 1998), Antiallergic (Kohda et al, 1985;Tasaka et al, 1988), Anti-inflammatory (Koyama et al, 1997), antihepatotoxic (Hirotani et al, 1986;Chen & Yu, 1993, inhibit the biosynthesis of cholesterol (Komoda et al, 1989), antioxidative and free radical scavenging effects (Lin, 2004) Ganoderma pfeifferi Bres.…”
Section: Flammulina Velutipes (Curtis) Singermentioning
confidence: 99%
“…Furthermore, exopolysaccharides produced by the submerged fermentation of the mycelium of V. volvacea can reduce the levels of serum TC, LDL cholesterol, and liver TC in alimentarially induced hypercholesterolemic rats . Fibers from F. velutipes (enokitake mushroom) and A. bisporus (button mushroom) can dramatically enhance the hepatic LDL receptor messenger RNA (mRNA), causing the diminution of the serum TC (Fukushima et al, 2000;Fukushima et al, 2001).…”
Section: Mushrooms As Hypocholesterolemic Agentsmentioning
confidence: 99%
“…White mushroom (Agaricus bisporus) is rich in acidic polysaccharides, dietary fiber, and antioxidants including vitamins C, B12, and D; folate; ergothioneine; and polyphenol (Fukushima et al 2000;Mattila et al 2001). This nutrient rich vegetable may have potential anti-inflammatory, hypoglycemic, and hypocholesterolemic effects.…”
Section: Introductionmentioning
confidence: 99%
“…4) Fukushima et al have also reported that sugar beet fiber lowered the serum total cholesterol level by enhancing hepatic LDL receptor mRNA. 5) Shortchain fatty acids (SCFAs), particularly propionate, a fermentable metabolite of soluble fiber, may be involved in lowering the serum cholesterol concentration. 6,7) The effect of fiber on plasma triacylglycerol is mainly from such gel-forming fiber as pectin which influences the functional properties of the intestinal mucosa by slowing upper intestinal transit.…”
mentioning
confidence: 99%